Ijtihad Maslahah Mursalah Tentang Harta Bersama Dalam Rumusan Hukum Perkawinan di Indonesia - hadi hidayaturrahman (Bayani, 2022)
The sacred fabric of marriage has a sacred position as well as determines many of the effects of family law, because marriage is not only an official and sacred instrument of illegitimate lawfulness, but becomes a large institution from which many effects of family law are built. Among the impacts of marriage is the management of property, especially regarding joint property in marriage. In principle, it is not found explicitly in the Qur'an and Al-Hadith regarding the mixing of property (joint property) in marriage. The issue of joint property in marriage began to emerge in the contemporary era as a symptom of the demands for equal rights between husband and wife, that the problem of property ownership in marriage often causes disputes. Through reading descriptive analysis with the theory of Ijtihad Maslahah Mursalah as part of the Ushul Fiqh method, it will provide an overview of the position of joint property in the classical era until it is contained in the formulation of marriage law in Indonesia today.